Cooperative voltage-balancing control for medium-voltage electric-spring system based on diode-clamped converter and dual active bridges - Yuan, Huawei (2023)
Electric spring (ES) is an emerging smart grid technology for stabilizing the voltage and frequency in a power network. Being fast demand-side-management technology, ES has recently been extended to the medium-voltage (MV) level in an ac-dc power conversion system that connects the distribution line of 6.6/11/22 kV to a dc grid of 800 V. To interface with the MV power grid, a diode-clamped converter (DCC) and multiple dual active bridges (DABs) can be employed to construct the MV-ES system. The balance of the capacitor voltages is crucial for DCCs, and thereby also for the MV-ES system. Conventional voltage-balancing approaches for DCCs generally compromise the quality of the grid-side voltage and current, which is undesirable especially in high-voltage high-power occasions. In this article, a voltage-balancing control solution is proposed for the MV-ES system via the cooperation of the DCC and DABs. By taking advantage of the DABs in voltage balancing, the DCC can adopt simple modulation and ensure grid-friendly voltage and current injection into the grid. The proposed voltage-balancing solution is verified using simulations in a five-level system and with practical experiments for a three-level system.